Representation Of Racism in The Film "Ip Man 4: The Finale" - Dezan Novhansa; Muhammad Zahran Gibran; Alfariza Alif Anggara; Budi Santoso; Firman Gilang Yoego Santoso; M. Afifulloh (Journal of English Language Teaching, Literatures, Applied Linguistic (JELTLAL), 2023)
Differences marked by skin color, body shape, hair color, etc. are the basis for the term 'race'. Such differences should be understood as racial pluralism not superiority. This plurality ultimately leads to a tendency to make stereotypical judgements and treat others based on such considerations. This research aims to find the issue of racism depicted in a film entitled "IP Man 4: The Finale". The researchers are interested in studying further the representation of racism issues through the media film. This research uses the semiotic theory proposed by Roland Barthes with a qualitative approach by making in-depth observations on each scene of the film. As a result, the researchers found that the racial practices depicted in the film "IP Man 4: The Finale" were racial separation efforts implemented at the time.